2019
DOI: 10.1093/tas/txz149
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the LIPEX finishing diet regimen on pork quality, fatty acid profile, palatability, and color stability12

Abstract: The objective of this study was to determine the effects of the LIPEX finishing diet regimen on pork chop n-3 polyunsaturated fatty acid (PUFA) content and fresh meat quality. Twenty-eight finishing pigs (PIC 359 × F1 Hermitage/NGT; initial BW 81.5 ± 2.55 kg) were subjected to a 49-d feeding trial. Treatments consisted of a 2 × 2 factorial design with Sex (n = 14 barrows and gilts each) and Diet as main effects. Dietary treatments consisted of a 2-phase standard finishing diet regimen or a 2-phase LIPEX finish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(60 reference statements)
1
1
0
Order By: Relevance
“…No difference (p > 0.05) was observed for the "off-flavor" attribute across loin chops from different oil sources, which agrees with the findings reported in other studies evaluating linseed, co-extruded flaxseed, and LIPEX feeding regimen (Gonzalez et al, 2020;Juárez Sheard et al, 2000). In contrast, previous studies showed that addingfish oil at relatively low levels (1 to 3 %) to pig diets led to off-flavor and odors in pig tissues and pork processed products (Leskanich et al, 1997;Øverland et al, 1996).…”
Section: Resultssupporting
confidence: 89%
“…No difference (p > 0.05) was observed for the "off-flavor" attribute across loin chops from different oil sources, which agrees with the findings reported in other studies evaluating linseed, co-extruded flaxseed, and LIPEX feeding regimen (Gonzalez et al, 2020;Juárez Sheard et al, 2000). In contrast, previous studies showed that addingfish oil at relatively low levels (1 to 3 %) to pig diets led to off-flavor and odors in pig tissues and pork processed products (Leskanich et al, 1997;Øverland et al, 1996).…”
Section: Resultssupporting
confidence: 89%
“…Meat quality is a term used to describe several meat properties that result from the interaction between ante and post-mortem muscle metabolism (Maltin, Balcerzak, Tilley & Delday, 2003;Durkin et al, 2009;Sima, Heres, Klont & Mireşan, 2015). Evaluating meat quality is an essential task for the industry, which aims to match the consumer demands of meat and meat products from different market niches, according to their quality (Sosnicki, Pommier, Klont, Newman & Plastow, 2003;Teixeira & Rodrigues, 2019;Gonzalez et al, 2020;Piórkowska et al, 2020).…”
Section: Introductionmentioning
confidence: 99%